Digital Literacy Key Performance Indicators for Sustainable Development - Danica Radovanović; Christine Holst; Sarbani Banerjee Belur; Ritu Srivastava; Georges Vivien Houngbonon; Erwan Le Quentrec; Josephine Miliza; Andrea S. Winkler; Josef Noll (Social Inclusion, 2020)
The concept of digital literacy has been defined in numerous ways over the last two decades to incorporate rapid technological changes, its versatility, and to bridge the global digital divide. Most approaches have been technology-centric with an inherent assumption of cultural and political neutrality of new media technologies. There are multiple hurdles in every stage of digital literacy implementation. The lack of solutions such as local language digital interfaces, locally relevant content, digital literacy training, the use of icons and audio excludes a large fraction of illiterate people. In this article, we analyse case studies targeted at under-connected people in sub-Saharan Africa and India that use digital literacy programmes to build knowledge and health literacy, solve societal problems and foster development. In India, we focus on notable initiatives undertaken in the domain of digital literacy for rural populations. In Sub-Saharan Africa, we draw from an original project in Kenya aiming at developing digital literacy for youth from low-income backgrounds. We further focus on Senegal, Mali, Burkina Faso and Tanzania, where field studies have been conducted on the use of digital technologies by low-literacy people and on how audio and icon-based interfaces and Internet lite standard could help them overcome their limitations. The main objective of this article is to identify key performance indicators (KPIs) in the context of digital literacy skills as one of the pillars for digital inclusion. We will learn how digital literacy programmes can be used to build digital literacy and how KPIs for sustainable development can be established. In the final discussion, we offer lessons learned from the case studies and further recommendation for stakeholders and decision-makers in the field of digital health literacy.